THE EFFECT OF BLEED WATER ON JT8D-15 ENGINE PERFORMANCE IN CRUISING CONDITION - Primadika Kampil (Institut Teknologi Dirgantara Adisutjipto, 2020)
Bleed air is an affected component of the performances engine. Bleed air is pressurized air taken from the compressor. On cruising condition, the bleed air is used for pressurization and AC (Air Conditioner). Because the decrease percentage of the pressure on the compressor, it will influence the value of other parameters. In this journal, the author discusses the effect of bleed air on JT8D-15 engine performance in cruising condition. The method used in this journal is Parametric Cycle Analysis of Real Engine through manual and numerical calculation methods. This research analyzed the performance of engine JT8D-15 within bleed air on and bleed air off condition which had been affected by variations of cruising altitude. The results of calculations from JT8D-15 engine performance and the effect of bleed air for thrust are higher when the aircraft's altitude rises, both in the bleed off and on condition. The values are at the altitude of 27000 ft, 31000 ft and 35000 ft when bleed on are 10638,668 lb, 10954,356 lb, 11266,251 lb, otherwise when bleed off are 10964,851 lb, 11278,715 lb, 11588,257 lb. SFC (specific fuel consumption) on bleed off has a lower value than the SFC value of bleed on.